DIAGNOSTIC SIGNIFICANCE OF LOCAL ALTERATIONS OF BRONCHIAL TREE IN THE COMPREHENSIVE SURVEY OF PATIENTS WITH PULMONARY TUBERCULOSIS - O. A. Serov; T. A. Kolpakova; V. A. Krasnov (Бюллетень сибирской медицины, 2013)
The difficulties in the interpretation of identified during bronchoscopy local bronchi alterations in patients with pulmonary tuberculosis make this problem of current interest. The comprehensive survey of 287 patients revealed the specific origin of local alterations of bronchial tree in 50% of patients with destruc-tive pulmonary tuberculosis and with bacterioexcretion